Virtual Identity, Plastic Identity. The „eighth Basque Province“ and the Genetically Imaginative Community - Volpi, Laura (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2019)
In this paper I propose to demonstrate how the anthropological view can highlight the effects of the relationship between ethnic nationalism and global processes. Showing the results of an ethnographical research conducted in 2015, I focus on the representation of social identity in the contemporary Basque Country. I emphasize the central role played by the new technologies for the identification of the Basque communities’ boundaries. The creation of „the eighth province“ (or province of the diaspora) shows how, in this context, Internet could transform the “imagined community” into a virtual reality. The ethnographical view proves to be useful to understand how local practices and discourses can interact with global phenomena: particularly significant is the spreading of archaeogenetic investigations in Euskal Herria, in order to verify the hypothesis of a reproductive isolation of Basque people. Moreover, a big part of local population is using genetic tests proposed online by DNA consulting agencies. It is important to identify how these genetic narratives are absorbed and reused by local populations and if they can reshape the past of a mnemonic community, influencing the representation of its future.
Keywords: Euskal Herria; nationalism; genetics; diaspora; identity; virtuality